Four-dimensional anatomical spinal reconstruction using pre-bent rods in thoracic adolescent idiopathic scoliosis - Akira Fukushima; Takashi Ohnishi; Terufumi Kokabu; Yuichiro Abe; Hiroyuki Tachi; Tsutomu Endo; Daisuke Ukeba; Norimasa Iwasaki; Katsuhisa Yamada; Hideki Sudo (Scientific Reports)
Abstract A four-dimensional (4D) anatomical spinal reconstruction (ASR) technique and anatomical notch-free, pre-bent rods have been developed for thoracic adolescent idiopathic scoliosis (AIS) surgery. We aimed to evaluate the outcomes of ASR using notch-free rods through multiple comparisons with conventional methods, including the simultaneous double-rod rotation technique (SDRRT) and ASR using manually bent notched rods. Three consecutive series of 126 patients who underwent surgery for Lenke 1 AIS curves were prospectively followed up for 2 years after surgery. The operative time was significantly shorter in the ASR using notch-free rods group than in the other two groups (P < 0.05). The correction rate of the main thoracic (MT) curve was higher in the ASR group than in the SDRRT group (P < 0.01). Thoracic kyphosis (TK) was greater in the ASR using notch-free rods group than in the other two groups at the final follow-up (P < 0.01). The percentage of patients with a T6–T8 location of the TK apex was greater in the ASR using notch-free rods group than in the SDRRT group at the final follow-up (P < 0.01). ASR using notch-free rods created an anatomical TK, contributing to a shorter operative time and standardization of the procedure.